A multidisciplinary approach to understanding the technology, opportunities, challenges, and implications for society of the metaverse - Slater, Mel; Di Dalmazi, Michele; Friedman, Doron; Galissaire, Jessica; Isaac, Henri; Kobusinska, Anna; Lopez-Tarruella-Martinez, Aurelio; Lamberti, Lucio; Lucas, Jean-François; Niamut, Omar Aziz; Pan, Xueni; Prié, Yannick; et al. (Frontiers in Virtual Reality, 2025)
Since late 2021, there has been increasing interest in the idea of the “metaverse.” This is a virtual, augmented or mixed reality system that potentially millions of people can simultaneously inhabit and where people can interact with one another in real-time, irrespective of the physical distance between them. It is heralded by some as the next-level world wide web that will use a 3D immersive interface, with the potential of mixing virtual and physical reality, with environments persisting over time and all interoperable between different platforms and devices. Nevertheless, there is still no true example of a metaverse, only a number of nascent examples. Here we discuss the technical foundations for such metaverses, the role of generative AI, and its possible impact on society—including education, healthcare and quality of life, business and consumers, the future of work, and its implications for democracy. We also discuss public perceptions of the metaverse, issues of governance and regulation, and its legal implications. Overall, while the metaverse may radically and positively alter the way that we live, we must take into account ethical and regulatory issues in order to avoid predictions of a dystopian future being realized. This study is, therefore, a multi-disciplinary introduction to the metaverse concept that may be useful to readers with many different interests.